Light within the Shade : Eight Hundred Years of Hungarian Poetry - Turner, Frederick, 1943-; Ozsváth, Zsuzsanna, 1931- (Book collections on Project MUSE., 2014)
Light within the Shade includes 135 of the most important Hungarian poems ranging from the fourteenth to the twenty-first century. "Organized in chronological order, the poems are followed by an essay by Ozsváth providing the historical, biographical, and cultural background of the poets and the poetry. The book concludes with Turner's essay on the special thematic and literary qualities of Hungarian poetry, as well as notes on translation practices. This essential volume exposes English-speaking readers to Hungarian poetry's artistic achievement in history and culture, its evolutionary development as a tradition, and its significance within the context of world literature."--Publisher.